PENGEMBANGAN MEDIA MODIFIKASI BUKU SAKU DIET SEIMBANG PENCEGAHAN DIABETES TIPE 2 PADA KADER DI DESA LEGOK KALER - Friandiny, Lutfhi; Lestari, Febri Sri (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Data for 2022, Sumedang Regency's type 2 diabetes mellitus population was 23,340. This is because educational media has not provided enough information regarding Type 2 Diabetes Mellitus. Cadres are a key component in enhancing public health, thus media education about eating a balanced diet to avoid Type 2 Diabetes Mellitus is necessary. Objective: To develop a Modified Pocket Book media regarding the prevention of Type 2 Diabetes Mellitus for Cadres in Legok Kaler Village. Methods: This study is an R&D (Research & Development) study using a development model using the 4D model (Define, Design, Development, Disseminate) data collection was carried out through in-depth interviews and questionnaires. Media development was carried out with material experts, media experts, and 36 cadres of Legok Kaler Village using the total sampling technique. Results: At the Development and Disseminate stages, the results of the feasibility test showed that 97% of material experts, 100% of media experts and 97% of cadres. Conclusion: The modified pocket book media is very suitable to be used as an educational media regarding a balanced diet to prevent Type 2 Diabetes Mellitus for cadres in Legok Kaler Village.